(untitled) (Bangladesh Journal of Botany, 2014)
The chromosome number and karyotype of three populations in Paeonia intermedia C.A. Mey are presented in this paper. The populations, sampled from Altai Prefecture in Xinjiang, China, are diploids (2n = 10), with 2A type karyotype and the karyotypic formula of 2n = 2x = 10 = 6m + 2sm + 2st. There was no obvious differentiation among all the three sections of the genus Paeonia based on parameters of arm ratio and ratio of the longest/shortest chromosome (L1/Ln). There is merely slight difference between the woody section (Sect. Moutan) and the herbaceous sections (Sects. Onaepia and Paeonia). DOI: http://dx.doi.org/10.3329/bjb.v43i1.19758 Bangladesh J. Bot. 43(1): 101-105, 2014 (June